Investigating the Impact of Flooding on Sanitation and Disease Outbreaks in South Sulawesi - Syamsih, Nur; Hasryanty, Sri; Rajam, Diah Ayu Lestari (Journal of Asian-african Focus in Health, 2025)
Flooding has long been recognized as a significant public health hazard, particularly in regions with inadequate sanitation infrastructure. This study investigates the impact of flooding on sanitation and disease outbreaks in South Sulawesi, Indonesia, using a quantitative approach. A sample of 400 households from urban, peri-urban, and rural areas was selected through stratified random sampling. Data were collected using structured surveys and secondary data from health centers and meteorological agencies. The study examined sanitation conditions before, during, and after flooding events, and the prevalence of waterborne and vector-borne diseases. Descriptive statistics, correlation analysis, and regression models were employed to analyze the data. Results revealed a substantial deterioration in sanitation conditions during flooding, with significant increases in the prevalence of waterborne (60%) and vector-borne diseases (50%) compared to pre-flooding levels. The correlation analysis indicated strong relationships between flooding intensity, poor sanitation, and higher disease prevalence. Regression models confirmed that flooding intensity and sanitation conditions were the primary predictors of disease outbreaks. These findings underscore the critical role of maintaining sanitation infrastructure during flooding and highlight the increased vulnerability of lower-income households. This study contributes to the literature on flood-induced health risks, offering valuable insights for disaster management and public health policy, particularly in developing regions facing similar challenges.